Therapeutic potential of Erxian decoction and its special chemical markers in depression: a review of clinical and preclinical studies - Ning-Xi Zeng; Ning-Xi Zeng; Han Li; Han Li; Meng-Yuan Su; Meng-Yuan Su; Xin Chen; Xiao-Yan Yang; Mei Shen (Frontiers Media S.A., 2024)
The increasing prevalence of depression is a major societal burden. The etiology of depression involves multiple mechanisms. Thus, the outcomes of the currently used treatment for depression are suboptimal. The anti-depression effects of traditional Chinese medicine (TCM) formulations have piqued the interest of the scientific community owing to their multi-ingredient, multi-target, and multi-link characteristics. According to the TCM theory, the functioning of the kidney is intricately linked to that of the brain. Clinical observations have indicated the therapeutic potential of the kidney-tonifying formula Erxian Decoction (EXD) in depression. This review aimed to comprehensively search various databases to summarize the anti-depression effects of EXD, explore the underlying material basis and mechanisms, and offer new suggestions and methods for the clinical treatment of depression. The clinical and preclinical studies published before 31 August 2023, were searched in PubMed, Google Scholar, China National Knowledge Infrastructure, and Wanfang Database. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Clinical studies have demonstrated that EXD exhibits therapeutic properties in patients with menopausal depression, postpartum depression, and maintenance hemodialysis-associated depression. Meanwhile, preclinical studies have reported that EXD and its special chemical markers exert anti-depression effects by modulating monoamine neurotransmitter levels, inhibiting neuroinflammation, augmenting synaptic plasticity, exerting neuroprotective effects, regulating the hypothalamic-pituitary-adrenal axis, promoting neurogenesis, and altering cerebrospinal fluid composition. Thus, the anti-depression effects of EXD are mediated through multiple ingredients, targets, and links. However, further clinical and animal studies are needed to investigate the anti-depression effects of EXD and the underlying mechanisms and offer additional evidence and recommendations for its clinical application. Moreover, strategies must be developed to improve the quality control of EXD. This review provides an overview of EXD and guidance for future research direction.